Supernatural beings of Pomerania: postmodern mapping of folkloristic sources - Włodzimierz Juśkiewicz; Jakub Jaszewski; Dariusz Brykała; Robert Piotrowski; K.M. Alexander; Kacper B. Juśkiewicz (Journal of Maps)
The 1:720,000 map ‘A New and Extensive Geographical Description of Supernatural Phenomena in Polish and German Pomerania’ (POMERANIÆ POLONICÆ ET GERMANICÆ PHÆNOMENA SUPERNATURALIA NOVA ET EMPLA DESCRIPTIO GEOGRAPHICA) presents the spatial distribution of supernatural beings along the Polish-German borderland. Depicted phenomena include devils, spirits, wild hunters, gnomes, will-o'-the-wisps, giants, dragons, mermaids, ghosts, werewolves, apparitions, and nightmares, based on the 19th and 20-century folkloric sources compiled into a geospatial database. The map combines GIS and linocut techniques with graphic symbols inspired by Renaissance cartography, including decorative cartouches and vignettes. Integrating modern cartometric methods with traditional styles, the map is both artistic and rich in information on cultural beliefs, blending historical and contemporary cartography for a unique perspective on folklore in this culturally diverse region.